Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.5012/bkcs.2008.29.6.1179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nanometer Sized Silver Materials on Biological Toxicity During Zebrafish Embryogenesis

Abstract: Commercial nanometer sized silver is widely used for its antibacterial effect; however, nanoparticles may also have ecotoxicological effects after being discharged into water. Nanometer sized silver can flow into aquatic environments, where it can exert a variety of physiologically effects in living organisms, including fish. The present study aimed to investigate the effect of nanometer sized silver on the development of zebrafish embryos, analyze the properties of commercial nanometer sized silver and define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The TiO 2 particles present no antibacterial activity. The test was performed on dark and it is reported that TiO 2 particles in dark condition present no antibacterial activity [12,15] which is consistent with our results. The six composites show antibacterial activity without light.…”
Section: Antibacterial Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The TiO 2 particles present no antibacterial activity. The test was performed on dark and it is reported that TiO 2 particles in dark condition present no antibacterial activity [12,15] which is consistent with our results. The six composites show antibacterial activity without light.…”
Section: Antibacterial Resultssupporting
confidence: 90%
“…It had been reported that photocatalytic and antimicrobial properties of TiO 2 can be improved by growing particles of a noble metal like Ag, Au or Cu over its surface or inside a matrix [12][13][14]. Composites of silver coatings over titanium dioxide nanoparticles are used in products to produce antibacterial activity [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, these antimicrobial nanoparticles always possess high biological toxicity and hard degradation, causing a series of secondary pollution and threat. For instance, some nanometer materials exhibit significant cytotoxicity to human and animal cells, so much so that they can damage the development of zebrafish embryo . For the hard-degradable nanomaterial, they can alter the bacterial community structure in a dose-dependent fashion, and influence taxa associated with ecosystem processes of N 2 fixation, methane oxidation, and complex C decomposition .…”
Section: Introductionmentioning
confidence: 99%
“…AgNPs have been shown to inhibit the growth of microorganisms and are potentially harmful to a wide variety of soil biota, plants, and aquatic organisms. , Although the mechanisms of AgNP toxicity are not yet fully understood, there are strong indications that the release of ionic silver (Ag + ) is a highly relevant factor in this respect , and that the formation of reactive oxygen species (ROS) may play a role in this.…”
Section: Introductionmentioning
confidence: 99%